The Potential of Networked Solidarity: Communication at the End of the Long Twentieth Century - Neff, G (MIT Press, 2018)
This chapter argues that the concerns of propaganda, voice, and democracy that characterized the rise of communication and media studies as disciplines were anchored in a set of twentieth-century liberal ideals that presumed the key role that information plays in people’s lives. This chapter argues that media and communication scholars need to update their theories for the twenty-first century. Both the election of Trump and the ‘Brexit’ referendum in the UK are case studies how twentieth century ideas about information, media and democracy are no longer sufficient to anchor contemporary media and communication scholarship. This chapter suggests a corrective by means an early twentieth century thinker who has not been used widely in media and communication, Emile Durkheim. By reintroducing the metaphor of organic and mechanical solidarity, this chapter argues that empathy and social cohesion might be alternates for intellectual anchors for our field for the future.